Topological classification of pairs of counter linear maps (in Ukrainian) - T. V. Rybalkina (Математичні Студії, 2013)
We consider pairs of linear mappings $(cal A,cal B)$ of theformsmallskipcenterline{$pudVW {cal A}{cal B} $} oi in which $V$ and $W$ arefinite dimensional unitary or Euclidean spaces over$mathbbC$ or $mathbbR$, respectively. Let $(cal A,calB)$ be transformed tosmallskipcenterline{$ pudV'W' {cal A'}{cal B'} $} oi by bijections$varphi_1colon Vo V'$ and $varphi_2colon Wo W'$. We saythat $(cal A,cal B)$ and $(cal A',cal B')$ are linearlyequivalent if $varphi_1$ and $varphi_2$ are linear bijectionsand topologically equivalent if $ varphi_1 $ and $ varphi_2 $are homeomorphisms. We prove that $(cal A,cal B)$ and $(calA',cal B')$ are topologically equivalent if and only if theirregular parts are topologically equivalent and their singularparts are linearly equivalent.